PREDICTING THE FUTURE OF QUANTITY SURVEYING PROFESSION IN THE CONSTRUCTION INDUSTRY - Joel Ochieng WAO (Journal of Construction Project Management and Innovation)
Quantity surveying profession has changed over time to adapt to the changing and increasing requirements of project owners. In the year 2007 to 2011, the construction industry experienced economic downturn causing uncertainty in the profession. This study examined the developmental trend of the quantity surveying profession in the construction industry to determine its future. The independent variable was the current level of satisfaction of quantity surveyors while the dependent variable was the future growth of the profession. The working hypothesis was that the profession would experience future growth. A survey questionnaire via Qualtrics online survey software was administered to quantity surveyors to determine their opinion of the profession. Data collected were analyzed using SAS v9.4 statistical analysis software. The results showed a greater level of satisfaction of quantity surveyors with the current developments in the profession. Further, the current level of satisfaction with the profession strongly correlated with the chances of growth of the profession, implying a greater likelihood of future growth in the roles of quantity surveyors in the next 10-15 years. Areas such as information technology and sustainable construction would favor the growth. Thus, the hypothesis was supported. Another finding was that females tended to be fewer in the profession. Thus, it was recommended that further research be conducted focusing on gender equality and propose ways to encourage women to join the quantity surveying profession. Overall, the study concluded that quantity surveyors should improve and diversify their roles more to provide greater value to project owners as the profession seemed promising.